0158 Loss of Connexin 36 Elicits Abnormalities in Thalamocortical Network Activity Relevant to Neuropsychiatric Disorders. (27th May 2020) - McNally, J M; Thankachan, S; Uygun, D S; Basheer, R
Abstract: Introduction: Neuronal gap-junctions are extensively expressed in mammalian forebrain and suggested to contribute to state-regulation and thalamocortical network activity. However, the physiological role of gap-junctions on these processes remains poorly understood. Connexin-36 (Cxn36) is highly expressed in the brain, representing a mechanism for electrical coupling of inhibitory neurons. We examined the effects of global Cnx36 deletion on sleep/wake and spontaneous and evoked EEG activity. Methods: We recorded in vivo EEG/EMG in Cxn36KO mice and littermate controls. Electrodes were stereotaxically implanted above frontal cortices. We analyzed sleep/wake states and algorithmically detected sleep spindles over 24 hours. Mice underwent auditory stimulation paradigms including the auditory steady state response (ASSR; 1 second train 20-50Hz clicks, 100 reps., 85dB) and mismatch negativity (MMN; 2.5kHz standard 90%, 10kHz deviant 10%, 300ms ISI, 90dB). Social behavior and investigation-evoked EEG activity were also assessed via the social habituation task (repeated 5 min exposures to novel mouse). Results: Cnx36KO mice exhibited limited sleep/wake abnormalities (n=7/group). Power spectra of EEG revealed significant impairments in spontaneous gamma-band activity (30-80Hz; All States, Light & Dark Phases), and beta activity (15-25Hz; All States, Light Phase). Sigma activity (10-15Hz) was significantly decreased (NREM and REM, Light phase). This was particularly pronounced during NREM-REM transitions. Despite no changes in spindle density, both spindle amplitude and duration were significantly decreased in Cnx36KOs. Cxn36KOs exhibited a blunted gamma-band response to acute ketamine (15mg/kg; IP), impaired 30 & 40Hz ASSR, and an abnormal response in the MMN task (decrease ERP peak amplitude & gamma). Finally, Cxn36KO mice exhibit impaired social habituation and significantly decreased investigation evoked slow gamma-band activity (30 - 55Hz). Conclusion: Our data suggest Cxn36 plays a critical role in regulating thalamocortical network activity. Further, impairments in Cnx36KO mice reflect abnormalities in neuropsychiatric disorders, including schizophrenia, implicating Cnx36 containing gap junctions as a novel therapeutic target. Support: Research supported by VA CDA Award BX002130 (JMM), VA Merit Awards BX004500 (JMM), BX001404 (RB), and NIMH RO1 MH39683 (Ritchie E. Brown).